Evaluation of Pairs Trading Performance on the Malaysian Stock Exchange - Woo, Chieh Kheng (2016)
Pairs trading is a market neutral strategy implemented in developed markets since the 1980s. Despite this, there has been a scarce amount of literature published on this subject. This study evaluates the performance of pairs trading strategy in the Malaysian context. A majority of studies on pairs trading yielded positive risk adjusted returns and it is not yet certain if a similar performance can be attained in Malaysia. Evidence from this study generally indicates positive risk adjusted performance using post-transaction costs data. The superior performance is more pronounced prior to accounting for transaction costs. There is no evidence to suggest industry homogeneity in pairs trading improves portfolio performance. Risk management techniques and their potential impact on the performance of the strategy are debatable based on prior studies. Pairs trading could serve as an effective trading strategy for investors in the Malaysian market.